Implementation of makerspaces in three Icelandic compulsory schools: Praxis and pedagogy, the first steps - Jónsdóttir, Svanborg R.; Kjartansdóttir, Skúlína Hlíf; Jónsdóttir, Svala; Pétursdóttir, Svava; Hjartarson, Torfi (Netla, 2021)
In the past few decades we have seen huge technological advancements, demographic shifts, economic expansion and profound cultural changes. The generations now growing up have been immersed in digital technology from their birth. We do, in our modern contemporary society, need a shift in education towards teaching and learning, where students are more active and creative participants, having the agency to shape their own learning. This research presents the first year of three in a school development project on implementing makerspaces to support such a shift in three compulsory schools in Reykjavík, the capital city of Iceland: Ingunnarskóli, Selásskóli and Vesturbæjarskóli (2019).Our study aims to increase understanding of what is needed for the innovation and design thinking of makerspaces to set roots in compulsory school practice and the pedagogies underlying “making” in school contexts. We want to identify characteristic and influential factors in the developmental process during the initial year of collaboration and implementation, as well as mapping how participants look upon and experience the project.Theoretical backgroundWe build our understanding and interpretation of the findings on theories and research on school and educational development (Fullan, 2019; Gerður G. Óskarsdóttir, 2014; Helga Sigríður Þórsdóttir and Anna Kristín Sigurðardóttir, 2020; Mason, 2008), digital technology and development of fab-labs and makerspaces (Blikstein, 2013; Halverson and Sheridan, 2014; Litts, 2015), creativity (Eisner, 2002), agency (Emirbayer and Mische, 1998; Moore, 2016; Svanborg R. Jónsdóttir og Rósa Gunnarsdóttir, 2017) and emancipatory pedagogy (Svanborg R. Jónsdóttir, 2012; Svanborg R. Jónsdóttir and Rósa Gunnarsdóttir, 2017).MethodThe research is grounded in qualitative methodology, where we seek to gain insight into participants’ attitudes and experiences and connect these to the focus of the research (Creswell, 2013). The research data consists of field notes, interviews with principals, project ...